Meningkatkan Aktivitas dan Hasil Belajar Melalui Penerapan Model Controvesial Issues Pada Pelajaran IPS - Maharani, Winda (FKIP Universitas Lampung, 2017)
Increasing student’s activities and learning outcomes by using controversial issues model in social studies. The aim of this study is for increasing the activities and outcomes of student’s social studies learning by using Controversial Issues Model. The kind of this study is a classroom action research, with the data collection’s forms are the observation and the test sheet. The analysis techniques used in this study are qualitative and quantitative analysis techniques. The results of this study showed that the implementation of Controversial Issues Model could increase the student’s learning activities and outcomes.The percentage of student’s mastery learning activities is 45% in the first cycle and become 75% in the second cycle. While at student’s learning outcomes increased from 65% in the first cycle to 80% in the second cycle. Keywords: controversial issues, activities and learning outcomes, social studiesDOI: http://dx.doi.org/10.23960/jpp.v7.i1.201701